PEMBINAAN KOPERASI YANG TIDAK SEHAT DI KABUPATEN SUMEDANG - dadang suhendi; Dea Santika; Deri Kurnia Sandi; Habib Rahman Aziz; Nadila Auliana Septianeu; Safitri Desriani (JRPA - Journal of Regional Public Administration, 2022)
This study aims to examine how the coaching or training in achieving unhealthy cooperative performance in Sumedang Regency. The method used in the preparation of this research report is a qualitative research method with a descriptive type. The sampling technique used was purposive sampling, with research informants: Head of Institutional and Human Resources Development Section, Head of Business Development Section, Head of Facilitation and Capital Section. Data collection techniques through library research and field studies. In analyzing the data, the Miles and Huberman model used the following steps: data reduction, data presentation, conclusion drawing/verification, and triangulation. Based on the results of the study, it was concluded that the implementation of the training was carried out well, in this case training for unhealthy cooperatives, the training included training to increase the capacity of Human Resources, and training related to the conditions experienced by the unhealthy cooperatives. There are several indicators that cause cooperatives to be unhealthy, such as: Not implementing the RAT which will cause the management and supervisors to not be held accountable, mandatory savings not running will affect business capital, inactive institutions will cause coordination and harmonization not to occur, and book 16 is not done which will lead to the loss of cooperative characteristics. The selection of training materials is seen from the unhealthy conditions of the cooperative, the selection of training methods is seen from the material taken and the condition of the cooperative's human resources. The resource persons taken from the training are competent speakers who have a Widyaiswara certificate and the participants of this training are members of unhealthy cooperatives. Procurement of this research must meet administration such as: identification, verification, making invitation letters, determining resource persons, and determining facilities and infrastructure. And have procedures that have been determined by the administrators/supervisors and participants. In determining the coaching, efforts are made to achieve the performance of unhealthy cooperatives into healthy cooperatives in Sumedang Regency.